Clinical evaluation of the efficacy and safety of fractional bipolar radiofrequency for the treatment of moderate to severe acne scars. Issue 1 (17th August 2015) - Verner, Ines
ABSTRACT: Several treatment modalities are used for the treatment of acne scars with variable results. Recent studies showed that fractional radiofrequency may be an effective treatment modality for acne scars. The objective of this study was to assess the efficacy, safety, tolerability and patient satisfaction of fractional bipolar radiofrequency (RF), the eTwo™ system (Syneron Candela Ltd., Yokneam, Israel) for treating acne scars. Twelve patients with moderate to severe acne scars received 3–5 treatments with the Sublative fractionated bipolar RF applicator of the eTwo device at 1‐month intervals. Patients were evaluated clinically and photographically at each visit and 3 months after the final treatment. Very good improvement (at least one scale) was seen after completing the five treatments. The patient satisfaction survey (Global Aesthetic Improvement Scale scores) revealed that half (6 out of 12) of the patients reported to be satisfied with treatment results, while the other half reported to be very satisfied. Beyond the expected erythema and minimal scab formation in the treated areas, which was mild and transient, none of the participants reported any adverse events. The data presented here support the high efficacy and safety of fractionated bipolar RF for the aesthetic improvement of moderate to severe acne scars.